Metode Pembelajaran Yang Terdaat Dalam Al-Qur'an - nur khofifah (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
This study aims to find out about the learning methods contained in the Al-Qur'an. Al-Qur'an as huda or guidance for mankind both in all fields without exception in the field of Education which contains the methods contained in the Al-Qur'an and has been practiced directly by the Prophet Muhammad through the guidance of the Al-Qur'an. this study. Using a descriptive qualitative method with a literature study approach where the data collected comes from books and journals that have been read and analyzed. The data analysis technique used is to read the required data sources which are taken when collecting data and then written in a descriptive form, namely describing the problem of the title so that readers can more easily understand and read it. This study describes clearly the methods contained in the Qur'an and contains verses of the Qur'an that are in accordance with the method discussed, and also explains the translation to make it easier to understand the verses that form the basis -Basic learning methods contained in the Qur'an.